Lecture by Michael E. Mendelsohn, MD, FACC Executive Director of the Molecular Cardiology Research Institute at TuftsÃÃÃ¥ÂNew England Medical Center, speaks to alumni at the School of Medicine. Photo 004 - Leonard, Spencer (Tufts Archival Research Center, 2008)
Lecture by Michael E. Mendelsohn, MD, FACC Executive Director of the Molecular Cardiology Research Institute at TuftsÃÃÃ¥ÂNew England Medical Center, speaks to alumni at the School of Medicine.